Differential gene expression by RNA-seq during Alzheimer's disease-like progression in the Drosophila melanogaster model. (July 2022) - da Costa Silva, Jéssica Regina; Fujimura, Patrícia Tieme; Batista, Letícia Leandro; Malta, Serena Mares; Filho, Romualdo Morandi; Silva, Matheus Henrique; de Souza, Aline Gomes; Silva, Ana Paula Mendes; Borges, Luiza Diniz Ferreira; Bastos, Victor Alexandre Félix; Cossolin, Jamile Fernanda Silva; Serrão, José Eduardo; et al.
Abstract: Alzheimer's disease (AD) is characterized by progressive, irreversible loss of memory and cognitive function. Drosophila melanogaster and other animal models are used to study several diseases, in order to elucidate unknown mechanisms and develop potential therapies. Molecular studies require biological samples and, for neuropathologies such as AD biopsy of the human brain, are invasive and potentially damaging. The solution is to use animal models, such as D. melanogaster, which is a model organism that can replace mammalian organisms in such studies. In this study, we evaluated the climbing ability and differential gene expression during AD progression due to the amylodoigenic pathway using RNA-seq, and we performed an in silico analysis of a fruit fly AD-like GFP (Green Fluorescent Protein) model with GFP expression in the pan-neural elav driver. A total of 1388 genes were differentially expressed in all analyzed groups. The main pathways related to those Differentially Expressed Genes (DEGs) during aging and AD progression were evaluated using the fly genes and human orthologs, in order to link genomic information to higher-order functional information with gene pathway mapping. We identified pathways present in all analyzed groups, such as metabolic pathways, ribosomal pathways, proteasome pathways and immune system pathways. Some of the genes were validated by qPCR. Knockdown of CG17754 gene by RNAi promoted degeneration in the fly eye, validating these findings in vivo. The identification of similarities in molecular pathways between the transgenic fly AD-like GFP model and mammals related to AD provides new insights into the use of this fly in screening novel anti-AD drugs. Highlights: Drosophila melanogaster  model for Alzheimer disease (AD-like) can be created by using elav-Gal4, UAS-GFP strain. AD-like model using elav-Gal4, UAS-GFP strain had a delay to beginning the symptoms. RNA-seq from AD-like GFP model showed a profile gene expressed similar to human. A novel gene, the  CG17754, was validated as candidate for neurodegeneration.